Comparison of cardiovascular response to sinusoidal and constant lower body negative pressure with reference to very mild whole-body heating - Ishibashi, Keita (BioMed Central, 2012)
BACKGROUND: The purpose of the present study was to compare sinusoidal versus constant lower body negative pressure (LBNP) with reference to very mild whole-body heating. Sinusoidal LBNP has a periodic load component (PLC) and a constant load component (CLC) of orthostatic stress, whereas constant LBNP has only a CLC. We tested two sinusoidal patterns (30-s and 180-s periods with 25 mmHg amplitude) of LBNP and a constant LBNP with −25 mmHg in 12 adult male subjects. RESULTS: Although the CLC of all three LBNP conditions were configured with −25 mmHg, the mean arterial pressure (MAP) results showed a significantly large decrease from baseline in the 30-s period condition (P <0.01). In contrast, the other cardiovascular indices (heart rate (HR), stroke volume (SV), cardiac output (CO), basal thoracic impedance (Z(0)), total peripheral resistance (TPR), the natural logarithmic of the HF component (lnHF), and LF/HF (ln(LF/HF))) of heart rate variability (HRV) showed relatively small variations from baseline in the 30-s period condition (P <0.01). The result of the gain and phase of transfer function at the sinusoidal period of LBNP showed that the very mild whole-body heating augmented the orthostatic responses. CONCLUSION: These results revealed that the effect of the CLC of LBNP on cardiovascular adjustability was attenuated by the addition of the PLC to LBNP. Based on the results of suppressed HRV response from baseline in the 30-s period condition, we suggest that the attenuation may be caused by the suppression of the vagal responsiveness to LBNP.